Agroforestry Indices Modeling for Sustainable Land Use Classiﬁcation in Huai Raeng-Khlong Peed Watershed, Trat Province, Thailand - Chaipong, Sukanya; Wachrinrat, Chongrak (Agriculture and Natural Resources, 2014)
Land use was modeled based on the sustainability of land uses in terms of biophysical aspects. The main objective of this study was to classify land use sustainability based on three agroforestry indices (organic matter, soil erosion and species diversity) which were determined using a weighting and rating score developed by experts from agroforestry, agriculture and government institutions. The relationship of the indices was established using a weighted linear combination technique to develop the model, and modeling was used to develop an agroforestry index (AFI). Site observation data were used in the AFI equation to obtain land use types under sustainability (ST) levels. The “highest” ST level was recorded for the home garden which was distributed over only 2 km2 (1.2% of the area), whist a “moderate” ST level was recorded for most land use types in the study area (124 km2, 73.4%) consisting of rambutan, mangosteen and para rubber plantations. Oil palm was at the “lowest” ST level. A “low” ST level was not found in the study area. Therefore, the highest ST level should be identiﬁed as the best land use; it could be developed from existing land uses or established as a new land use in the study area. This study provided information to help identify priorities with regard to land use types and the sustainable land characteristics that can be useful for managers and planners in local and central governments and in other nongovernmental organizations.